Tackling Disability Discrimination in the United Kingdom: The British Disability Discrimination Act - Charlotte Pearson; Nick Watson (Washington University Journal of Law & Policy, 2007)
The social position of disabled people in the United Kingdom, as elsewhere in the developed world, has changed dramatically in the past twenty years. Disabled people are no longer forced into confinement in long-term institutions, increasingly more disabled children are being educated in mainstream schools, and employment rates for disabled people are rising. Despite these improvements there is still considerable evidence to suggest that disabled people in the United Kingdom are subjected to discrimination. This Essay provides an overview of the development of disability discrimination legislation in the United Kingdom over the past two decades. While highlighting early attempts to challenge the practice in the employment context, this Essay also explores the more recent adoption of a framework for anti-discrimination legislation. Although the United Kingdom has made significant progress in integrating an anti-discrimination agenda into key areas of social life, attitudinal and structural change has been considerably slower. This Essay seeks first to unravel the key debates underpinning legislative change. Discussion then moves to an exploration of the critique of the United Kingdom legislation from the disability movement. This highlights a broader focus on the definitions applied, and contrasts the approach taken by successive British governments with other international frameworks. The Essay concludes by arguing that the focus of antidiscrimination legislation needs to move beyond issues of definition and instead integrate a stronger emphasis on promoting the civil rights of disabled people and recognizing the diversity of identities.
Keywords: Discrimination against people with disabilities -- Law & legislation; Disabled persons; Handicapped discrimination; United Kingdom. Disability Discrimination Act 1995; United Kingdom